2005
DOI: 10.1063/1.1847215
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and magnetic properties of sintered NdFeB magnets with improved impact toughness

Abstract: An effort to increase the impact toughness of Nd–Fe–B sintered magnets by adding small amounts of Al, Nd, Ga, Cu, and Nb was successful. No significant compromise to magnetic properties occurred. Based on this work, a series of sintered Nd–Fe–B magnets with improved toughness was developed, which we call ToughNEO™. Small precipitates, which may contribute to the improvement of toughness, were observed using scanning electron microscope for all samples with improved toughness. Tumbling and drilling tests furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…The average particle size decreases from 2.77 m to 2.33 m as the Pr addition content increases from 0 to 100 wt%. This is because the toughness of the strip casting ribbons becomes lower with the decreases of Nd content [11,12]. In the jet milling process, the ribbons with higher Pr content are easily crushed into fine particle size powder, which means that fine JM powders could be obtained by increasing the Pr content in the alloys.…”
Section: Resultsmentioning
confidence: 99%
“…The average particle size decreases from 2.77 m to 2.33 m as the Pr addition content increases from 0 to 100 wt%. This is because the toughness of the strip casting ribbons becomes lower with the decreases of Nd content [11,12]. In the jet milling process, the ribbons with higher Pr content are easily crushed into fine particle size powder, which means that fine JM powders could be obtained by increasing the Pr content in the alloys.…”
Section: Resultsmentioning
confidence: 99%
“…The impact resistance is one of the key factors that influence the reliability of brittle materials during commercial use. Liu et al and Liu et al reported [7,8] that impact toughness of sintered Nde FeeB magnets can be significantly improved by increasing the contents of Nd and doping elements such as Nb, Cu, Al, etc. The change of the mechanical properties after rare-earth element substitution such as Pr and Dy in sintered NdeFeeB magnets has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some applications of magnets for structural elements that require magnets to operate under mechanical stresses have been limited due to the insufficient strength of currently available magnets. Further improvement in strength and toughness of magnets will widen the fields of application [7,8]. In this paper, effects of the hydrogen desorption process on magnetic properties and fracture strength of sintered NdFeB were investigated.…”
Section: Introductionmentioning
confidence: 99%